1975
DOI: 10.1002/cpt1975175515
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tricyclic antidepressants and alcohol on psychomotor skills related to driving

Abstract: Twenty healthy subjects took amitriptyline, doxepin, and placebo for 2 wk each in a double-blind crossover trial, and another 20 subjects similarly took nortriptyline, chlorimipramine, and placebo. The antidepressants were given three times daily in doses generally used for neurotic patients. The presence of antidepressants in tissues was checked with the tyramine pressor test. On the seventh and fourteenth days of each period, psychomotor skills (choice reaction, coordination, and attention) were measured aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
1

Year Published

1984
1984
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 6 publications
3
15
0
1
Order By: Relevance
“…Although there are no previous studies reported which are directly comparable with the present one, our results are broadly compatible with the findings of Seppala et al (1975) and Seppala (1977). These workers used lower doses of amitriptyline but the subjects were studied during 2 weeks of treatment.…”
Section: Total Choice Reaction Time (Crt; Figure 2)supporting
confidence: 93%
See 2 more Smart Citations
“…Although there are no previous studies reported which are directly comparable with the present one, our results are broadly compatible with the findings of Seppala et al (1975) and Seppala (1977). These workers used lower doses of amitriptyline but the subjects were studied during 2 weeks of treatment.…”
Section: Total Choice Reaction Time (Crt; Figure 2)supporting
confidence: 93%
“…Patients tend to become tolerant to the sedative effects of drugs during chronic treatment, and it could be argued that the adverse effects of ethanol on psychomotor performance might be more serious and more easily detected when examined on a background of only minor drug-related sedation. In fact, the available evidence suggests that the impairment of performance by both antidepressant and ethanol diminishes during the course of a few weeks' treatment with the drugs Seppala et al, 1975;Seppala, 1977 …”
Section: Total Choice Reaction Time (Crt; Figure 2)mentioning
confidence: 99%
See 1 more Smart Citation
“…While studies of the interaction of alcohol with benzodiazepines are common (and often arrive at different conclusions), the interaction of alcohol with antidepressants has been studied tess frequentIjy: The effect of tricyclic antidepressants and alcohol on psychomotor skills related to driving was examined by Seppala et al (1975). While the individual drugs failed to impair the psychomotor skills combination of alcohol with amitriptyline and with doxepin impaired performance in cumulative choice reaction times and the latter drug also increased errors in reaction time.…”
Section: Discussionmentioning
confidence: 99%
“…12 Several studies have shown that alcohol potentiates the sedative effects of TCA. 13,14 The aim of the present study was to investigate whether milnacipran has any influence on neurosensory vigilance during car driving.…”
Section: Introductionmentioning
confidence: 99%